Profiling the reactivity of cyclic C-nucleophiles towards electrophilic sulfur in cysteine sulfenic acid. Issue 1 (19th October 2015) - Gupta, Vinayak; Carroll, Kate S.
Abstract : Oxidation of a protein cysteine thiol to sulfenic acid, termed S -sulfenylation, is a reversible post-translational modification that plays a crucial role in regulating protein function and is correlated with disease states. Abstract : Oxidation of a protein cysteine thiol to sulfenic acid, termed S -sulfenylation, is a reversible post-translational modification that plays a crucial role in regulating protein function and is correlated with disease states. The majority of reaction-based small molecule and immunochemical probes used for detecting sulfenic acids are based on the 5, 5-dimethyl-1, 3-cyclohexanedione (dimedone) scaffold, which is selective, but suffers from low reactivity. In addition, mechanistic details and features that diminish or enhance nucleophile reactivity remain largely unknown. A significant hurdle to resolving the aforementioned issues has been the chemically unstable nature of small-molecule sulfenic acid models. Herein, we report a facile mass spectrometry-based assay and repurposed dipeptide-based model to screen a library of cyclic C-nucleophiles for reactivity with sulfenic acid under aqueous conditions. Observed rate constants for ∼100 cyclic C-nucleophiles were obtained and, from this collection, we have identified novel compounds with more than 200-fold enhanced reactivity, as compared to dimedone. The increase in reactivity and retention of selectivity of these C-nucleophiles were validated in secondary assays, including a protein model for sulfenic acid. Together, this work represents a significant step toward developing new chemical reporters for detecting protein S -sulfenylation with superior kinetic resolution. The enhanced rates and varied composition of the C-nucleophiles should enable more comprehensive analyses of the sulfenome and serve as the foundation for reversible or irreversible nucleophilic covalent inhibitors that target oxidized cysteine residues in therapeutically important proteins.